2022
DOI: 10.23887/jet.v6i2.46102
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Kahoot! for Japanese Language Learning in Indonesian High School

Abstract: Kahoot! is an individual and collaborative gamified learning platform that encourages curiosity, promotes lifelong learning, and makes learning enjoyable. Given the numerous advantages of using Kahoot! in language acquisition, several academic institutions have included gamification to enhance their learning experience. However, there are always issues and hurdles encountered throughout technology deployment. The present study aimed to analyze how the teacher implements Kahoot! in Japanese learning, the Indone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In the context of online learning, these discussions can be challenging for students without sufficient digital devices, unstable & unaffordable internet connection, and low motivation (Artini et al, 2020;Dantes, Audina et al, 2022;Dantes, Rinawati, et al, 2022;Purwanti et al, 2022;Suwastini, Nalantha, et al, 2021). Meanwhile, low-motivated students can easily evade collaborative discussions by pinning a lousy internet connection or device error as their excuses (Dantes, Rinawati et al, 2022;Eva et al, 2022;Suwastini, Nalantha et al, 2021). Dwiyanti &Ersani et al (2021) suggested that detailed feedback could motivate students to participate more.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of online learning, these discussions can be challenging for students without sufficient digital devices, unstable & unaffordable internet connection, and low motivation (Artini et al, 2020;Dantes, Audina et al, 2022;Dantes, Rinawati, et al, 2022;Purwanti et al, 2022;Suwastini, Nalantha, et al, 2021). Meanwhile, low-motivated students can easily evade collaborative discussions by pinning a lousy internet connection or device error as their excuses (Dantes, Rinawati et al, 2022;Eva et al, 2022;Suwastini, Nalantha et al, 2021). Dwiyanti &Ersani et al (2021) suggested that detailed feedback could motivate students to participate more.…”
Section: Discussionmentioning
confidence: 99%
“…They could use various online platforms beyond the classroom for autonomous learning (Dincer, 2020;Hazaymeh, 2021;Saputra et al, 2021;Putra, 2021;Rahmayanti et al, 2021). Online learning also allows the teacher to integrate technology tools to boost the learners' autonomy, such as blogging and online quizzes (Eva et al, 2022;Lee, 2016;Matsubara & Yoshida, 2018). In this case, the learners select their learning strategy, access the materials, and find the sources independently outside class time.…”
Section: Figure 2 Benefits Of Online Learningmentioning
confidence: 99%
“…This shows that games are able to build up intrinsic motivation that comes from within a person. By using gamificationincorporating games into an educational contextstudents will not only enjoy the process of learning, but also improve their performance as a form of increased motivation (Adnyani et al, 2022;Kalogiannakis & Papadakis, 2019). By being aware of the facts concerning students' motivation in learning and teaching process in the COVID-19 pandemic, this study aims to improve students' motivation in learning English through gamification in online learning settings.…”
Section: Introductionmentioning
confidence: 99%